Anti-inflammatory activity of ethanolic seed extract of gogo (Entada phaseoloides L.) - Agustin, Marie Joyce Anne P.; Due, Maryrose Aridel Ayna P. (2009)
Entada phaseoloides (gogo) is a folkloric medicinal used as an anti-inflammatory, anti-rheumatic, anti-ulcer, counter irritant agent among the natives of Cordillera. It is also believed to cure jaundice, abdominal and colic pains and edema due to malnutrition. Its barks are used for making shampoos againts dandruffs. (Co, 1984). In-vitro analysis was performed to know the possible active components of gogo againts inflammation which includes BateSmith and Metcalf method and Wilstatter "cyanidin" test for flavonoids. In-vivo analysis, on the other hand, was done to know its effect on induced inflammation on the paws of mice. Statistical analysis was conducted to know the significant differences in the sizes of the paw injected with the control, commercial drug (Aspirin) and the plant extract itself. Positive results that include the occurrences of leucoanthocyanin, cyanidin and y-benzopyrone nucleus confirmed flavonoids to be present in the ethnolic extract. Results from the carrageenan induced rat paw edema showed that the plant extract is effective in inhibiting the inflammation similar to Aspirin. The data gathered were confirmed to be significant in stating that E. phaseoloides is indeed an agent against inflammation with the help of the statistical tools used. -- Authors abstract.